Kapasitas Absorpsi sebagai Variabel Moderator dalam Perusahaan Logistik di Indonesia - Osama Rizqi Amriyasaldi; Teofilus; Timotius Febry Christian Wahyu Sutrisno; David Sukardi Kodrat (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study examines the role of Absorptive Capacity (ACAP) as a moderating factor in the relationship between Organizational Change Capability (OCC), Strategic Alliance (SA), and Sustainable Competitive Advantage (SCA) among logistics service companies in Indonesia. The research addresses the phenomenon where logistics firms, despite adopting change initiatives, often struggle to transform learning capability into effective alliances that secure long-term competitiveness. Using a quantitative survey, the findings reveal that learning capability within OCC does not directly drive strategic alliances, yet alliances remain a significant pathway toward achieving sustainable competitive advantage. Importantly, ACAP strengthens these relationships by enabling organizations to acquire, assimilate, and exploit external knowledge more effectively. This suggests that logistics firms need to build strong absorptive mechanisms to transform knowledge into collaborative advantage. The study is limited by its relatively small sample size and its focus on logistics companies in major Indonesian cities, which may restrict the generalizability of results to other sectors or regions. Despite this limitation, the research contributes to the understanding of how ACAP supports inter-organizational collaboration, offering insights for managers seeking to enhance strategic partnerships and maintain competitiveness in a dynamic business environment.